Student vehicle registration system (SVRS) - Siti Aisyah , Abd Mutalip (2014)
Safety factor in the university is very important. In order to make sure the safety of the university and campus areas, UMP Security Department will need a system to record the information of student including their vehicle's information. Vehicle registration system is developed to keep information of all student registered vehicles in the campus. The objective of this project is to develop an online student vehicle registration system and produce the official university vehicle's sticker. This project will focus on managing all student and vehicle information and also generate QR code on vehicle sticker based on the information that is registered in the system such as student matric number and their vehicle plate number. The system is expected to help the security staff to detect whether the vehicle is registered or unregistered by scanning the QR code on the sticker and match the information with the owner of vehicle and matric number. The student vehicle registration is developed using PHP and Xampp to run the MySQL server.